A Genomic Perspective on the Origin and Emergence of SARS-CoV-2 - Zhang, Yong-Zhen; Holmes, Edward C. (Cell, 2020)
The ongoing pandemic of a new human coronavirus, SARS-CoV-2, has generated enormous global concern. We and others in China were involved in the initial genome sequencing of the virus. Herein, we describe what genomic data reveal about the emergence SARS-CoV-2 and discuss the gaps in our understanding of its origins.